Age at Seroconversion, HLA Genotype, and Specificity of Autoantibodies in Progression of Islet Autoimmunity in Childhood - Bauer, Witold; Veijola, Riitta; Lempainen, Johanna; Kiviniemi, Minna; Härkönen, Taina; Toppari, Jorma; Knip, Mikael; Gyenesei, Attila; Ilonen, Jorma (The journal of clinical endocrinology and metabolism, 2019)
Abstract Context Children with initial autoantibodies to either insulin (IAA) or glutamic acid decarboxylase (GADA) differ in peak age of seroconversion and have different type 1 diabetes (T1D) risk gene associations, suggesting heterogeneity in the disease process. Objective To compare the associations of age at seroconversion, HLA risk, and specificity of secondary autoantibodies with the progression of islet autoimmunity between children with either IAA or GADA as their first autoantibody. Design and methods A cohort of 15,253 children with HLA-associated increased risk of T1D participated in a follow-up program in which islet autoantibodies were regularly measured. The median follow-up time was 6.7 years. Spearman correlation, Kaplan-Meier survival plots, and Cox proportional-hazard models were used for statistical analyses. Results Persistent positivity for at least one of the tested autoantibodies was detected in 998 children; 388 of children progressed to clinical T1D. Young age at initial seroconversion was associated with a high probability of expansion of IAA-initiated autoimmunity and progression to clinical diabetes, whereas expansion of GADA-initiated autoimmunity and progression to diabetes were not dependent on initial seroconversion age. The strength of HLA risk affected the progression of both IAA- and GADA-initiated autoimmunity. The simultaneous appearance of two other autoantibodies increased the rate of progression to diabetes compared with that of a single secondary autoantibody among subjects with GADA-initiated autoimmunity but not among those with IAA as the first autoantibody. Conclusions Findings emphasize the differences in the course of islet autoimmunity initiated by either IAA or GADA supporting heterogeneity in the pathogenic process. Young age at initial islet autoantibody seroconversion in childhood associates with a high risk of further progression to T1D in IAA-initiated autoimmunity but not in GADA-initiated autoimmunity.